2019
DOI: 10.31832/smj.535573
|View full text |Cite
|
Sign up to set email alerts
|

Bir Şehir Hastanesi Kan Transfüzyon Merkezine Başvuran Donörlerde HBV, HCV, HIV ve VDRL Seroprevalansı

Abstract: Öz Amaç Kan ve kan ürünleri transfüzyonu sonrasında en sık karşılaşılan komplikasyon kullanılan ürünlerden bu-laşan enfeksiyonlardır. Kan ve kan ürünleri transfüzyonu sonrasında hepatit B virüsü, hepatit C virüsü ve insan immün yetmezlik virüsünün (HIV) neden olduğu enfek¬siyonlar halen en önemli sağlık problemi olmaya devam etmektedir. Bu nedenle; HBsAg, anti-HCV, anti-HIV ve Treponema pallidum'a yönelik RPR (Rapid Plasma Re¬agin) veya VDRL (Venereal Disease Research Labora¬tory) gibi tarama testleri kan tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(2 reference statements)
0
0
0
Order By: Relevance
“…7,9,10,18 According to studies reported from different regions of Türkiye, anti-HCV positivity rate in blood donors varies between 0.15% and 0.92%. 15 In a study conducted in Aydın (the province where our study took place), anti-HCV positivity in blood donors was reported as 0.16%. 19 A fieldwork study in Türkiye revealed that 1% of the adult population has anti-HCV positivity.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…7,9,10,18 According to studies reported from different regions of Türkiye, anti-HCV positivity rate in blood donors varies between 0.15% and 0.92%. 15 In a study conducted in Aydın (the province where our study took place), anti-HCV positivity in blood donors was reported as 0.16%. 19 A fieldwork study in Türkiye revealed that 1% of the adult population has anti-HCV positivity.…”
Section: Discussionmentioning
confidence: 86%
“…8 According to studies reported from different regions of Türkiye, anti-HIV positive rate in blood donors varies between 0% and 1.06%. 15 In the study where the seroprevalence of anti-HIV was 1.06%, the prevalence of HIV infection was found to be 0.002% after HIV confirmation testing was performed. 21 In our study, HIV infection was found in 14 (4%) of 344 patients with AGWs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation